2018
DOI: 10.1016/j.cell.2018.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy in Intestinal Epithelial Cells Triggers Adaptive Immunity during Tumorigenesis

Abstract: In colorectal cancer patients, a high density of cytotoxic CD8 T cells in tumors is associated with better prognosis. Using a Stat3 loss-of-function approach in two wnt/β-catenin-dependent autochthonous models of sporadic intestinal tumorigenesis, we unravel a complex intracellular process in intestinal epithelial cells (IECs) that controls the induction of a CD8 T cell based adaptive immune response. Elevated mitophagy in IECs causes iron(II)-accumulation in epithelial lysosomes, in turn, triggering lysosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 56 publications
2
72
0
1
Order By: Relevance
“…The role of STAT3 in carcinogenesis is controversial: studies have demonstrated that STAT3 can function either as an oncoprotein or a tumor suppressor in the same cell type, depending on the specific genetic background or presence/absence of specific coexisting biochemical defects [44]. In the AOM and the Apc (Min/+) mouse models of colorectal cancer, the deletion of STAT3 in the intestinal epithelial cells reduced early adenoma formation (i.e., oncogenic role) [45, 46]. However, ablation of STAT3 in the later stage of tumor progression significantly increased the invasiveness of the tumors and decreased the survival of the animals (i.e., tumor suppressor role) [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of STAT3 in carcinogenesis is controversial: studies have demonstrated that STAT3 can function either as an oncoprotein or a tumor suppressor in the same cell type, depending on the specific genetic background or presence/absence of specific coexisting biochemical defects [44]. In the AOM and the Apc (Min/+) mouse models of colorectal cancer, the deletion of STAT3 in the intestinal epithelial cells reduced early adenoma formation (i.e., oncogenic role) [45, 46]. However, ablation of STAT3 in the later stage of tumor progression significantly increased the invasiveness of the tumors and decreased the survival of the animals (i.e., tumor suppressor role) [45].…”
Section: Discussionmentioning
confidence: 99%
“…In the AOM and the Apc (Min/+) mouse models of colorectal cancer, the deletion of STAT3 in the intestinal epithelial cells reduced early adenoma formation (i.e., oncogenic role) [45, 46]. However, ablation of STAT3 in the later stage of tumor progression significantly increased the invasiveness of the tumors and decreased the survival of the animals (i.e., tumor suppressor role) [45]. Since low surface expression of CD80 is an immunoescape mechanism of colon carcinoma [47], we speculate that the tumor suppressor role of STAT3 in the later stages of colon cancer progression may be explained by its ability to enhance CD80 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although 96% of all CRCs do not develop in the context of pre-existing inflammation, the roles of chronic inflammation, tumor-elicited inflammation, the tumor microenvironment (TME), and partially adaptive immune cells in CRC development, have been established, particularly in the context of their interaction with gut dysbiosis [18][19][20][21][22][23]. Colitis-associated cancer (CAC) is a specific subset of CRC characterized by its implication with inflammation that accounts for 1%-2% of all CRCs [24].…”
Section: Origins Of Crcmentioning
confidence: 99%
“…However, an opposing report indicated that increased expression of IP3R3 stimulated cancer cell survival by promoting cellular metabolism [ 104 ]. Mice with colon cancer, driven by mutations of the gene encoding β-catenin, undergo a STAT3-dependent increase in aerobic glycolysis and suppression of ETC activity, which are mediated by the upregulated expression of HIF-1α and Myc [ 67 , 105 ]. The mechanism of how STAT3 regulates mitochondrial activity is not yet clear; however, specifically targeting mitochondrial activity is postulated to suppress tumor growth.…”
Section: Regulation Of Metabolic Signaling Pathway Through Stat3 Imentioning
confidence: 99%